2017
DOI: 10.3390/bioengineering4020025
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Alkali Pre-Treatment, Densification and Enzymatic Saccharification of Canola Straw and Oat Hull

Abstract: The effects of microwave-assisted alkali pre-treatment on pellets’ characteristics and enzymatic saccharification for bioethanol production using lignocellulosic biomass of canola straw and oat hull were investigated. The ground canola straw and oat hull were immersed in distilled water, sodium hydroxide and potassium hydroxide solutions at two concentrations (0.75% and 1.5% w/v) and exposed to microwave radiation at power level 713 W and three residence times (6, 12 and 18 min). Bulk and particle densities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 50 publications
8
29
0
Order By: Relevance
“…Specifically, experimental run#2 (900 W, 15 min, 5% w/v) achieved the lowest solid and glucan recovery but highest lignin removal, while run#4 (300 W, 5 min, 5% w/v) achieved the highest solid and glucan recovery but lowest lignin removal. The results indicated that microwave power and irradiation time significantly impacted the degradation of lignin and glucan, consistent with Agu, Tabil, and Dumonceaux (), Akhtar, Goyal, and Goyal (), Boonsombuti, Luengnaruemitchai, and Wongkasemjit () and Nomanbhay et al (),…”
Section: Resultssupporting
confidence: 82%
“…Specifically, experimental run#2 (900 W, 15 min, 5% w/v) achieved the lowest solid and glucan recovery but highest lignin removal, while run#4 (300 W, 5 min, 5% w/v) achieved the highest solid and glucan recovery but lowest lignin removal. The results indicated that microwave power and irradiation time significantly impacted the degradation of lignin and glucan, consistent with Agu, Tabil, and Dumonceaux (), Akhtar, Goyal, and Goyal (), Boonsombuti, Luengnaruemitchai, and Wongkasemjit () and Nomanbhay et al (),…”
Section: Resultssupporting
confidence: 82%
“…The sugar production cost was highly sensitive to changes in fungal pretreatment time, glucose yield, and bulk density ( Figure 6 [87][88][89][90][91][92][93][94][95][96][97][98][99]). Variations in the fungal pretreatment time between 7 and 60 days, which are the minimum and maximum values reported in the fungal pretreatment literature used as a data source (Section 2.1.1), produced the greatest change on the sugar production cost for perennial grasses, corn stover, and agricultural residues ( Figure 6).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Assuming a higher bulk density reduced the volume of the equipment needed throughout the facility, hence decreasing the sugar production cost. For example, in the case of chopped agricultural residues, the bulk density of wheat straw has been reported around 50-100 kg/m 3 [62,95], while canola straw has shown a bulk density of around 140-160 kg/m 3 [94]. Assuming the bulk density in the higher range for agricultural residues decreased the sugar production cost by 11%, while assuming the bulk density in the lower range increased the sugar production cost from 2.0 to 3.1 $/kg ( Figure 6C).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Agricultural and forest residues as well as industrial and municipal solid wastes are made up of lignocellulosic components [2]. They are environmentally friendly with a carbon-neutral footprint when converted to renewable energy, compared to fossil energy sources such as crude oil, coal, and natural gas [3]. Lignocellulose biomass consists of cellulose, hemicellulose, and lignin.…”
Section: Introductionmentioning
confidence: 99%
“…An effective pretreatment technique is needed to liberate the cellulose from lignin, reduce cellulose crystallinity, and increase cellulose porosity [11]. Various pretreatment methods have been developed according to different research studies [3], but the choice of pretreatment technique for a raw material/feedstock is influenced by many factors. These include sugar recovery yield, low moisture content effectiveness, lignin recovery, required particle size, and low energy demand [20].…”
Section: Introductionmentioning
confidence: 99%